First geochemical and geochronological characterization of Late Cretaceous mesosilicic magmatism in Gastre, Northern Patagonia, and its tectonic relation to other coeval volcanic rocks in the region - Zaffarana, Claudia Beatriz (2018)
Fil: Zaffarana, Claudia B. Consejo Nacional de Investigaciones Científicas y Técnicas. Buenos Aires, Argentina.